THE DETERMINANT OF FINANCIAL HEALTH ON SHARIA LIFE INSURANCE COMPANY (Empirical Research on Sharia Life Insurance Company in Indonesia Period 2010-2015) - Primayanti, Asih; Arfianto, Erman Denny (Faculty of Economics and Business Diponegoro University, 2016)
Financial health is a term used to describe the state of one's personal or company financial situation. Considering the many factors that affect the level of health of the company, this research will develop research to analyze the effect of Firm Size (siz), Investment Performance (IP), Liquidity Ratio (LR), Incurred Loss Ratio (ILR) on Financial Health of Sharia Insurance company. The purpose of this study was to determine and analyze the factors that affect the Financial Health of Sharia Life Insurance Company in Indonesia the period 2010 to 2015.The Financial Health measured by two methods, namely by Altman Zscore and the second with a Risk Based Capital (RBC) with Firm Size (siz), Investment Performance (IP), Liquidity Ratio (LR), Incurred Loss Ratio (ILR) as independent variables . Samples used in this study as many as 14 Sharia Life Insurance, where the method used is purposive sampling is a sampling method that takes an object with certain criteria and using cross section data, where every year the amount of data taken is not same. Analysis of data using multiple regression analysis.The results of data analysis or regression results indicate that simultaneous Firm Size (siz), Investment Performance (IP), Liquidity Ratio (LR), and Incurred Loss Ratio (ILR) affects Financial Health (Z) and Financial Health (RBC). While partially produced different results, which is only variable Investment Performance (IP) which partially affects Financial Health (Z), but on the Financial Health (RBC), Investment Performance (IP), Liquidity Ratio (LR), Incurred Loss Ratio ( ILR) partially affect the Financial Health (RBC). The magnitude of the coefficient of determination (adjusted R-square) Financial Health (Z) is equal to 0.376. This means that 37.6% dependent variable, namely the Financial Health 1 (Z) can be explained by four independent variables, ie variables Firm Size (siz), Investment Performance (IP), Liquidity Ratio (LR), Incurred Loss Ratio (ILR) while the remaining 62.4% level Financial Health (Z) is explained by variables or other causes beyond the model. Then, magnitude of the coefficient of determination (adjusted R-square) Financial Health (RBC) is approximately 0.567. This means that 56.7% dependent variable 2, namely the Financial Health (RBC) can be explained by four independent variables are variables Firm Size (siz), Investment Performance (IP), Liquidity Ratio (LR), Incurred Loss Ratio (ILR) while the remaining 43.3% Financial Health (RBC) is explained by variables or other causes beyond the model.